Adsorption Properties of Beta Carotene from Activated Carbon Derivatives of Oil Palm Empty Bunches - Jasmidi, Jasmidi; Zubir, Moondra; Selly, Rini; Faradilla, Putri; Rahmah, Siti (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
This research aims to determine the adsorption ability of activated carbon and Fe-Cu modified activated carbon in the β-carotene adsorption process on Crude Palm Oil (CPO). Empty Palm Oil Bunches (TKKS) are used as a bio-sorbent for carbon production at a temperature of 500 ºC. The synthesized carbon was activated using H3PO4 and modified with Fe-Cu metal. CPO quality parameters such as Free Fatty Acids and Peroxide Number were analyzed to see the effect of adsorption on CPO quality. The β-carotene level in the CPO sample used is 472.1 ppm. The optimum conditions for using activated carbon in the β-carotene adsorption process are a mass variation of 8 grams with the β-carotene remaining after adsorption being 432.4 ppm, whereas by using Magnetic Activated Carbon, CPO β-carotene after adsorption remains at 426.1 ppm. Meanwhile, increasing the adsorption time causes the absorption of β-carotene to become greater. By using Activated Carbon the remaining β-carotene is 300.1 ppm after 120 minutes, whereas by using Magnetic Activated Carbon the optimum absorption time is faster and the amount of β-carotene absorbed is greater. The remaining βcarotene after absorption with Magnetic Activated Carbon was 288.7 after 90 minutes of adsorption. Apart from being able to absorb β-carotene, magnetic activated carbon is also better at reducing FFA and PV levels from CPO.